2004
DOI: 10.1103/physreva.70.033803
|View full text |Cite
|
Sign up to set email alerts
|

Erbium-implanted high-Qsilica toroidal microcavity laser on a silicon chip

Abstract: Lasing from an erbium-doped high-Q silica toroidal microcavity coupled to a tapered optical fiber is demonstrated and analyzed. Average erbium ion concentrations were in the range 0.009-0.09 at. %, and a threshold power as low as 4.5 W and an output lasing power as high as 39.4 W are obtained from toroidal cavities with major diameters in the range 25-80 m. Controlling lasing wavelength in a discrete way at each whispering-gallery mode was possible by changing the cavity loading, i.e., the distance between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
79
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(83 citation statements)
references
References 33 publications
4
79
0
Order By: Relevance
“…For further details on this theoretical optimum threshold, we refer the reader to Ref. 11. We found that for a toroid with a principal diameter of 60 m and intrinsic quality factor ͑pump mode͒ between 5 ϫ 10 6 and 1 ϫ 10 7 , thresholds in the range of 400-600 nW can be achieved with an Er 3+ concentration of 2 ϫ 10 19 cm −3 .…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…For further details on this theoretical optimum threshold, we refer the reader to Ref. 11. We found that for a toroid with a principal diameter of 60 m and intrinsic quality factor ͑pump mode͒ between 5 ϫ 10 6 and 1 ϫ 10 7 , thresholds in the range of 400-600 nW can be achieved with an Er 3+ concentration of 2 ϫ 10 19 cm −3 .…”
mentioning
confidence: 95%
“…11 This optimal erbium ion concentration depends, in turn, on the intrinsic quality factor of the pump mode. 11 In the low concentration limit, the threshold power increases sharply because Er 3+ ions are not able to give sufficient gain required for loss compensation; while in high concentration limit, the threshold again increases due to increases of concentrationdependent loss mechanism, such as upconversion and ionpair induced quenching. For further details on this theoretical optimum threshold, we refer the reader to Ref.…”
mentioning
confidence: 99%
“…This rule of thumb is well-known and can be rigorously derived for a Fabry-Perot cavity [15][16][17]. Similar out coupling criteria in the absence of self-saturation have also been used for fiber-coupled microcavity lasers [18][19][20].…”
mentioning
confidence: 99%
“…Although we did not www.intechopen.com attempt it for GaAs, a CALTECH group devised a laser baking process for achieving ultrahigh Q values of multi-millions involving a SiO2 microcavity. It is interesting to be a toroidal microcavity whose 3D WCM properties is unknown yet (Armani et al, 2003;Min et al, 2004). Fig.…”
Section: Basic Properties Of Pqr Lasersmentioning
confidence: 99%